2016
DOI: 10.1021/acs.jpcc.6b07983
|View full text |Cite
|
Sign up to set email alerts
|

Desorption-Mediated Motion of Nanoparticles at the Liquid–Solid Interface

Abstract: Nanoparticles (NPs) confined in thin layers of liquid within liquid cells used for in situ transmission electron microscopy (TEM) move very slowly, in contrast to free particles in bulk liquid. The reason is still poorly understood. Here, we tracked gold NPs moving in water at the liquid−solid interface with in situ TEM at rates of 100 frames per second. The recorded motion exhibited three key features: (1) it was made up of sustained sequences of "sticky" motion where NPs only moved a few nanometers each time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
116
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(122 citation statements)
references
References 75 publications
6
116
0
Order By: Relevance
“…S1 (b)] that is marked by stacked Au NPs. We expect that the primary role of the substrate is to suppress the Brownian motion [35] [36]. In bulk NP solution, we measure the diffusion coefficient D = 1.6· 10 -12 m 2 /s via dynamic light scattering, and the equivalent force is expected to be orders of magnitude larger than the mutual Lorentz force calculated here.…”
Section: (A)mentioning
confidence: 99%
“…S1 (b)] that is marked by stacked Au NPs. We expect that the primary role of the substrate is to suppress the Brownian motion [35] [36]. In bulk NP solution, we measure the diffusion coefficient D = 1.6· 10 -12 m 2 /s via dynamic light scattering, and the equivalent force is expected to be orders of magnitude larger than the mutual Lorentz force calculated here.…”
Section: (A)mentioning
confidence: 99%
“…During TEM measurements, the electron beam induces a positive charge onto the Si 3 N 4 window and the induced surface charge affects the motion of the charged nanoparticles . Liu et al demonstrated that the movement of positively charged (cetyltrimethylammonium (CTA)) and negatively charged (citrate) gold nanoparticles is significantly different because of the positively charged window surface .…”
Section: Nanoparticle Motionmentioning
confidence: 99%
“…Thus, nanoparticles with induced dipoles are adsorbed onto the wall surface. Chee et al discovered that gold nanoparticles exhibit sticky motion, so that the particles only move a few nanometers with rotational motion on the Si 3 N 4 surfaces ( Figure a,b) . When the absorbed nanoparticles were desorbed from the window with thermal vibration, they flew ≈50 nm and stuck again with fast pivoted rotations.…”
Section: Nanoparticle Motionmentioning
confidence: 99%
“…It has been reported that the high energy electron beam can knock away electrons in the insulating SiN x membrane, making it positively charged, whose charge may then be partially transferred to a nano object on the window and let the nano object be electrostatically repelled from the surface. [30,48] It can be expected that the electron irradiation would cause charge build-up in the imaged region ( Figure 4B). [30] These charge effect would be more obvious in the thin liquid region, as the electrical charges shall be harder to get carried away by the thinner fluid layer.…”
Section: Formation Of Pt Nanoclusters In a Thin Liquid Regionmentioning
confidence: 99%